Repetitive Diving in Trained Rats Still Increases Fos Production in Brainstem Neurons after Bilateral Sectioning of the Anterior Ethmoidal Nerve - McCulloch, Paul F.; Warren, Erik A.; DiNovo, Karyn M. (Frontiers in Physiology, 2016)
This research was designed to investigate the role of the anterior ethmoidal nerve (AEN) during repetitive trained diving in rats, with specific attention to activation of afferent and efferent brainstem nuclei that are part of this reflexive response. The AEN innervates the nose and nasal passages and is thought to be an important component of the afferent limb of the diving response. Male Sprague-Dawley rats (N=24) were trained to swim and dive through a 5 m underwater maze. Some rats (N=12) had bilateral sectioning of the AEN, others a Sham surgery (N=12). Twelve rats (6 AEN cut and 6 Sham) had 24 post-surgical dive trials over 2 hrs to activate brainstem neurons to produce Fos, a neuronal activation marker. Remaining rats were non-diving controls. Diving animals had significantly more Fos-positive neurons than non-diving animals in the caudal pressor area, ventral medullary dorsal horn, ventral paratrigeminal nucleus, nucleus tractus solitarius, rostral ventrolateral medulla, Raphe nuclei, A5, Locus Coeruleus, and Kölliker-Fuse area. There were no significant differences in brainstem Fos labeling in rats diving with and without intact AENs. Thus the AENs are not required for initiation of the diving response. Other nerve(s) that innervate the nose and nasal passages, and/or suprabulbar activation of brainstem neurons, may be responsible for the pattern of neuronal activation observed during repetitive trained diving in rats. These results help define the central neuronal circuitry of the mammalian diving response.